Madrasah Management Effectiveness in Improving Madrasah Quality : (Case Study of the Leadership Role of Madrasah Principals) - Saila Rachmawati (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2021)
The world of Pesantren is always interesting and it is endless to continue to be discussed and discussed. Because in it there are many uniqueness that cannot be found in other Educational Institutions besides pesantren. The pesantren which is meant here is the pesantren kholafi (pesantren which contains religious knowledge and also general knowledge). In the modern era like today, most parents prefer to leave their children in school and send them to educational institutions that have and pay attention to religious content. The concerns that arise must also be balanced with awareness of the massive changes taking place. So that individuals who live and experience shifting demands today are not wrong steps in responding to all the changes that exist. The development of educational institutions is inseparable from the role of the leader who holds the control of an educational institution. This study has the aim that the founders of madrassas or Islamic boarding schools can adopt the methods or strategies of other pesantren so that they can continue to have an existence in the middle of this millennial era. This study uses qualitative research methods, namely by collecting data, documents and interviews with several speakers. The method used in this study is a qualitative approach that is research whose information is obtained by describing the phenomena that exist. The data collection techniques using observation, interviews, and documents.